Metrological aspects of researching the specific contact resistivity of ohmic contacts by using the four-contact method - Sheremet, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
In this paper, we have considered the four-contact method for measurements of the specific contact resistivity of the ohmic contacts (ρc). The presented method for measuring ρc has been compared with several other methods. Limits of applying this method have been shown.